2021
DOI: 10.1017/s175502032100040x
|View full text |Cite
|
Sign up to set email alerts
|

Operands and Instances

Abstract: Can conjunctive propositions be identical without their conjuncts being identical? Can universally quantified propositions be identical without their instances being identical? On a common conception of propositions, on which they inherit the logical structure of the sentences which express them, the answer is negative both times. Here, it will be shown that such a negative answer to both questions is inconsistent, assuming a standard type-theoretic formalization of theorizing about propositions. The result is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The argument is sometimes named after both Russell and Myhill, since it was rediscovered, apparently independently, by Myhill (1958). A more detailed presentation of this argument in the present setting of plural propositional quantification can be found in Fritz (forthcoming b).…”
Section: The Inconsistency Of Immediate Groundmentioning
confidence: 99%
See 1 more Smart Citation
“…The argument is sometimes named after both Russell and Myhill, since it was rediscovered, apparently independently, by Myhill (1958). A more detailed presentation of this argument in the present setting of plural propositional quantification can be found in Fritz (forthcoming b).…”
Section: The Inconsistency Of Immediate Groundmentioning
confidence: 99%
“…It can also be shown that this inconsistency essentially arises out of combining these two principles, as each of them is consistent on its own. I do so in Fritz (forthcoming b).…”
Section: The Inconsistency Of Immediate Groundmentioning
confidence: 99%